Stalker - Hoel, Jon (Constellations Ser., 2021)
Andrei Tarkovsky's Stalker (1977) is arguably the most thoughtful science fiction film ever made. This book attempts to unravel its complexities, : its difficult production, its composition and cinematography, the many philosophies it engages with, the cultural and historical landscapes that cultivated it, and the enormity of its influence.